Microextraction and gas chromatography/mass spectrometry for improved analysis of geosmin and other fungal "off" volatiles in grape juice - Morales-Valle, H. (2010)
Geosmin is a volatile fungal metabolite with an earthy aroma produced in grape products from rotten grapes. The accumulation of geosmin in grapes is caused by the interaction of Botrytis cinerea and Penicillium expansum. Solid Phase Microextraction (SPME) has great utility for collecting volatile compounds in wine. However, contamination with earthy odours may have occurred previously in the must and novel methods are required for this commodity. In the present report, several parameters of the SPME were evaluated to optimize geosmin extraction. The method permitted quantification of geosmin and other fungal volatiles by Gas Chromatography–Mass Spectrometer (GC–MS) at very low concentrations. Limits of detection and quantification (LD and LQ) for geosmin were 4.7 ng L−1 and 15.6 ng L−1 respectively. The RSD was 4.1% and the recovery rates ranged from 115% to 134%. Uniquely, haloanisoles were analyzed by using only one internal standard (2,3,6-trichloroanisole) thus avoiding the synthesis of deuterated anisole analogues that are used as internal standard in other methods. The method was used for the analysis of grape juice samples inoculated with B. cinerea and P. expansum. Geosmin and methylisoborneol were the compounds that appeared to contribute most to earthy odours, although other fungal compounds which are claimed to cause earthy or mouldy off-odours were detected (e.g. 1-octen-3-ol and fenchol).